Analysis of Teachers' Competence in the Application of Islamic Storytelling Methods: A Case Study at ABA Nyai Ahmad Dahlan Kindergarten - Dwi Hastuti; Indriani, Fitri; Ali, Raden Muhammad; Susilo, Zulfa Mumtaz; Maziya, Nur (TA`DIBUNA, 2026)
This study aims to analyze the competence of teachers in applying Islamic storytelling methods at ABA Nyai Ahmad Dahlan Kindergarten as part of early childhood Islamic character formation. A qualitative approach with a case study design was employed, and data were collected through in-depth interviews, observations, and documentation. Data analysis followed three stages: data reduction, data presentation, and conclusion drawing. The results indicate that teachers possess a solid understanding of Islamic values and are able to integrate these values effectively into the stories they convey. They demonstrate skills in composing stories, selecting appropriate supporting media such as hand puppets, books, and videos, and using voice intonation to maintain children’s attention. Children’s responses to this method were highly positive, reflected in their enthusiasm during storytelling sessions and observable improvements in attitudes after the stories. Despite these strengths, the study identified several challenges, including limited teaching aids, less conducive classroom conditions, and minimal formal training opportunities for teachers. Nevertheless, teachers show strong commitment to enhancing their storytelling competence through self-reflection, sharing best practices with colleagues, and independently seeking additional learning resources. This study concludes that teachers’ competence in Islamic storytelling plays a significant role in supporting the formation of children’s character. To optimize this contribution, continuous professional development and adequate institutional support are necessary. These findings are expected to serve as a reference for the systematic development of Islamic character education in early childhood education programs.